The universal Sua5/TsaC family evolved different mechanisms for the synthesis of a key tRNA modification - Pichard-Kostuch, Adeline; Da Cunha, Violette; Oberto, Jacques; Sauguet, Ludovic; Basta, Tamara (Frontiers in Microbiology, 2023)
TsaC/Sua5 family of enzymes catalyzes the first step in the synthesis of N6-threonyl-carbamoyl adenosine (t6A) one of few truly ubiquitous tRNA modifications important for translation accuracy. TsaC is a single domain protein while Sua5 proteins contains a TsaC-like domain and an additional SUA5 domain of unknown function. The emergence of these two proteins and their respective mechanisms for t6A synthesis remain poorly understood. Here, we performed phylogenetic and comparative sequence and structure analysis of TsaC and Sua5 proteins. We confirm that this family is ubiquitous but the co-occurrence of both variants in the same organism is rare and unstable. We further find that obligate symbionts are the only organisms lacking sua5 or tsaC genes. The data suggest that Sua5 was the ancestral version of the enzyme while TsaC arose via loss of the SUA5 domain that occurred multiple times in course of evolution. Multiple losses of one of the two variants in combination with horizontal gene transfers along a large range of phylogenetic distances explains the present day patchy distribution of Sua5 and TsaC. The loss of the SUA5 domain triggered adaptive mutations affecting the substrate binding in TsaC proteins. Finally, we identified atypical Sua5 proteins in Archaeoglobi archaea that seem to be in the process of losing the SUA5 domain through progressive gene erosion. Together, our study uncovers the evolutionary path for emergence of these homologous isofunctional enzymes and lays the groundwork for future experimental studies on the function of TsaC/Sua5 proteins in maintaining faithful translation.